Evaluasi Tata Kelola Teknologi Informasi Menggunakan COBIT 5 Pada Hotel Dan Resort XYZ - Darmayanti, Nyoman Citra; Putra, I Gede Juliana Eka; Artani, Ketut Tri Budi (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
The use of Information Technology (IT) has become very important in improving the effectiveness and efficiency of company operations, including WakaGangga Hotel and Resort. They implemented a PMS (Property Management System) system to coordinate the activities of hotel departments. Despite implementing an integrated information system, the company faces several problems, delays in handling risks such as data input errors, system errors, and slow system performance, in addition to communication barriers with the center. This study aims to assess the maturity level of IT governance at WakaGangga Hotel and Resort using the COBIT 5 framework, focusing on domains EDM03, APO12, and APO02. Data collection methods involve interviews, observations, and questionnaires. The results provide recommendations for improvement based on the audit results using COBIT 5.